A burst of protein sequence evolution and a prolonged period of asymmetric evolution follow gene duplication in yeast - Scannell, Devin R.; Wolfe, Kenneth H. (Genome Research, 2007)
It is widely accepted that newly arisen duplicate gene pairs experience an altered selective regime that is often manifested as an increase in the rate of protein sequence evolution. Many details about the nature of the rate acceleration remain unknown, however, including its typical magnitude and duration, and whether it applies to both gene copies or just one. We provide initial answers to these questions by comparing the rate of protein sequence evolution among eight yeast species, between a large set of duplicate gene pairs that were created by a whole-genome duplication (WGD) and a set of genes that were returned to single-copy after this event. Importantly, we use a new method that takes into account the tendency for slowly evolving genes to be retained preferentially in duplicate. We show that, on average, proteins encoded by duplicate gene pairs evolved at least three times faster immediately after the WGD than single-copy genes to which they behave identically in non-WGD lineages. Although the high rate in duplicated genes subsequently declined rapidly, it has not yet returned to the typical rate for single-copy genes. In addition, we show that although duplicate gene pairs often have highly asymmetric rates of evolution, even the slower members of pairs show evidence of a burst of protein sequence evolution immediately after duplication. We discuss the contribution of neofunctionalization to duplicate gene preservation and propose that a form of subfunctionalization mediated by coding region activity-reducing mutations is likely to have played an important role.
10.1101/gr.6341207